Perbedaan Kecanduan Media Sosial Tiktok pada Remaja Pengguna Aktif dan Pasif - Chandra, Sonia Dewi (Orasi: Jurnal Ilmu Politik dan Sosial, 2024)
The purpose of the study was to see the difference in the level of TikTok social media addiction in active and passive user adolescents. Quantitative method was used in this study. The purposive sampling technique or setting certain criteria as a sample in the study is a sampling technique in this study. The subjects in this study were 342 respondents who were in the middle age adolescent group. The TikTok social media addiction scale was used as a method of data collection. Data were analyzed using non-parametric, namely mann whitney u-test. The results of this study indicate that there is a significant difference in TikTok addiction in active and passive user adolescents with a sig value. 2 tailed 0.003 (P < 0.05).